A Click‐Functionalized Single‐Molecule Magnet Based on Cobalt(II) and Its Analogous Manganese(II) and Zinc(II) Compounds. Issue 3 (22nd December 2014) - Plenk, Christian; Krause, Jasmin; Rentschler, Eva
Abstract: A mononuclear Co II single‐molecule magnet suitable for click chemistry was investigated. [M(oda)(aterpy)] complexes (oda 2– = oxodiacetate, aterpy = 4′‐azido‐2, 2′:6′, 2″‐terpyridine) with M = Mn II, Zn II, and Co II were synthesized as azide‐functionalized building blocks for the copper‐catalyzed azide–alkyne cycloaddition reaction. The required structural integrity of the complexes in solution was proven in great detail by using ESI‐MS and NMR spectroscopy. For the six‐coordinate [Co(oda)(aterpy)] complex, single‐molecule magnet behavior was confirmed with an effective energy barrier of 4.2 cm –1 . Abstract : An azide‐functionalized single‐molecule magnet suitable for click reactions is reported. The solution stability of three novel building blocks containing single Co II, Mn II, and Zn II metal ions is proven in great detail by using ESI‐MS and NMR spectroscopy. Remarkably, alternating current susceptibility data of the six‐coordinate cobalt(II) complex reveal single‐molecule magnet behavior.